Religious Education Faces the Challenge of Religious Plurality A Qualitative-Empirical Study in Vienna - Klutz, Philipp (2016)
This study examines the internal discourse on religious education (RE) at two secondary schools in Vienna using a qualitative empirical method. At these schools RE have reached their oraganisational limits. The study has made a major contribution to religious education sensitive to contexts by exploring the most times implicit attitudes towards religion and RE from teachers and from members of the school community board.